MANIFESTATIONS OF PERUVIAN SOCIETY TAKEN TO THE FICTION OF FILM, BETWEEN THE SECOND HALF OF THE 20TH CENTURY AND THE BEGINNING OF THE 21ST CENTURY - DE LA CRUZ-VILLANUEVA, Carlos (2024)
The The following research work addresses some scope and manifestations of Peruvian cinema from the second half of the 20th century to the beginning of the 21st century, under the synthesis and historical analysis, with the aim of understanding the revealing nature of the films in addressing a diversity of complex social phenomena, under its fictitious audiovisual narratives, inspired by the reality that shelters them. In this journey, it is important to consider that this synthesis raises the vitality of this historical source, in portraying varied aspects of society and in turn feeding these narratives back to various generations in time and space. Observed the disseminating and elaborating nature of Peruvian films, whose discourses stimulate and constitute partial formators of the collective imagination and transfer social elements that constitute or form part of the national collective memory.